What dreams were made of : movie stars of the 1940s - Griffin, Sean (Star decades: American culture/American cinema., 2011)
What Dreams Were Made Of examines the performers who helped define American cinema in the 1940s, a decade of rapid and repeated upheaval for Hollywood and the United States. Through insightful discussions of key films as well as studio publicity and fan magazines, the essays in this collection analyze how these actors and actresses helped lift spirits during World War II, whether in service comedies, combat films, or escapist musicals. Together, they represented the hopes and fears of a nation during turbulent times, enacting on the silver screen the dreams of millions of moviegoers.